EXTH-81. ITGA5 IS A NOVEL IMMUNOTHERAPEUTIC TARGET AGAINST TREATMENT REFRACTORY MEDULLOBLASTOMA. (14th November 2022) - Bakhshinyan, David; Suk, Yujin; Kuhlman, Laura; Adile, Ashley; Ignatchenko, Vladimir; Gwynne, William; Custers, Stefan; Macklin, Andrew; Venugopal, Chitra; Kislinger, Thomas; Singh, Sheila
Abstract: Medulloblastoma (MB) is the most common type of malignant pediatric brain cancer. Current standard of care (SOC) involves maximal safe resection and neuraxis radiotherapy and chemotherapy in individuals older than 3 years. To date, these cytotoxic SOC combined with craniospinal irradiation led to devastating neurocognitive and developmental deficits impacting quality of life for pediatric patients. The biological heterogeneity of MB is highlighted by the existence of four distinct molecular subgroups (WNT, SHH, Group 3, and Group 4). Group 3 and Group 4 have the poorest patient outcomes because of their aggressive, metastatic nature, and so often remain treatment refractory to SOC. Group 3 has a poor prognosis due to its high incidence of leptomeningeal spread and an overall survival rate of less than 50%. The cytotoxic nature and lack of response in specific subtypes to SOC underscores the urgent need for developing and translating novel treatment options including immunotherapies. In our earlier work, we have developed a therapy-adapted patient derived xenograft (PDX) model of the Group 3 MB as the tumor cells undergoes therapy in vitro and in vivo . N-glycocapture surfaceome profiling of the MB cells through this PDX model identified Integrin α5 (ITGA5) as one of the most differentially expressed targets found at recurrence when compared to engraftment and untreated timepoints. Through shRNA knockdown and small molecule inhibition, we identify ITGA5 expression marks a MB cell subpopulation with increased self-renewal ability both in vitro and in vivo . Access to recurrent MB (rMB) post-therapy allowed us to investigate the changes in the surfaceome of MB cells using proteomics profiling to identify promising rMB-specific targets for rational development of novel immunotherapies.